Optimizing the component ratio of PEDOT:PSS by water rinse for high efficiency organic solar cells over 16.7 - Li, Qicong; Sun, Yang; Yang, Cheng; Liu, Kong; Islam, Md. Rasidul; Li, Long; Wang, Zhijie; Qu, Shengchun (Science bulletin, 2020)
A new method by water rinse to modify PEDOT:PSS was developed, demonstrating a 16.75% PCE in organic solar cells. [Display omitted] For the state-of-the-art organic solar cells (OSCs), PEDOT:PSS is the most popularly used hole transport material for the conventional structure. However, it still suffers from several disadvantages, such as low conductivity and harm to ITO due to the acidic PSS. Herein, a simple method is introduced to enhance the conductivity and remove the additional PSS by water rinsing the PEDOT:PSS films. The photovoltaic devices based on the water rinsed PEDOT:PSS present a dramatic improvement in efficiency from 15.98% to 16.75% in comparison to that of the untreated counterparts. Systematic characterization and analysis reveal that although part of the PEDOT:PSS is washed away, it still leaves a smoother film and the ratio of PEDOT to PSS is higher than before in the remaining films. It can greatly improve the conductivity and reduce the damage to substrates. This study demonstrates that finely modifying the charge transport materials to improve conductivity and reduce defeats has great potential for boosting the efficiency of OSCs.